Pelaksanaan Supervisi Kepala Sekolah Dalam Meningkatkan Kinerja Guru Pendidikan Agama Islam Di SMA Negeri 1 Indralaya - Meita Angraini (UNISAN JURNAL, 2024)
This research aims to explore the implementation of principal supervision in improving the performance of Islamic Religious Education teachers at SMA Negeri 1 Indralaya. The research method used is qualitative with a case study approach. Data was collected through participant observation, in-depth interviews, and document analysis. Respondents consisted of school principals, teachers and supervisory staff. Data analysis was carried out using data reduction, data display and data verification techniques. The results of the research show that the implementation of supervision by the school principal has made a positive contribution in improving the performance of Islamic Religious Education teachers. Supervision is carried out on a scheduled and ongoing basis, with a focus on developing teacher professionalism. Principals use a collaborative approach in providing feedback to teachers, facilitating reflective discussions, and providing needed resources. Apart from that, the school principal also implements a supervision model that is in accordance with the characteristics of Islamic Religious Education subjects. However, there are still several challenges in implementing supervision, such as lack of adequate time, limited resources, and resistance from some teachers. Therefore, it is recommended that school principals continue to improve communication and collaboration with teachers, provide more intensive supervision training, and expand collaboration networks with related institutions. This research contributes to the understanding of school principal supervision practices in the context of Islamic Religious Education. The practical implication of this research is the important role of school principals in helping teachers improve their performance through effective and continuous supervision. Apart from that, this research can also be a basis for developing policies and training programs for school principals and teachers in improving the quality of religious education in high schools.